SOME FEATURES OF CURRENT TECHNOGENIC MOVEMENTS OF THE EARTH’S CRUST - V. Yu. Timofeev; D. G. Ardyukov; A. V. Timofeev; E. V. Boyko; M. G. Valitov; E. N. Kalish; Yu. F. Stus; D. A. Nosov; I. S. Sizikov (Геодинамика и тектонофизика)
We describe the history of studying the current crustal movements by various methods and discuss technogenic effects recorded at large water-reservoir zones and mineral deposits in Siberia. Initially, classical surveying techniques aimed to obtain high-accuracy ground-based measurements of height, tilt and direction. Modern geodesy techniques and methods for measuring absolute gravity are now available to investigate displacement, deformation, tilt and other phenomena taking place on the Earth’s surface. These methods are used to estimate kinematic parameters of the crust areas (e.g. rates of subsidence and horizontal movements) and to monitor fluid motions in mineral deposits. Such data are critical for ensuring a proper management of the mineral deposits. In this article, we analyse technogenic processes observed in the Ust Balyk oil-gas field, the Zapolyarny gas deposit, the water-reservoir zone at the Sayano-Shushenskaya hydroelectric power station (SSHPS) on the Yenisei river, and large open-pit mines in the Kuzbass basin. Our analysis is based on surface displacement rates estimated from the data collected in different periods of observations at large man-made facilities. In the study of the hydro technical objects, we estimated the displacement rates at 5.0 mm per year. In the northern areas of the West Siberian petroleum basin, subsidence rates amounted to 20–25 mm per year in the early 2000s. These estimates were supported by the high-accuracy gravity measurements showing an increase up to 6–7 microGal per year in the oil-gas field development areas. We assess a possibility of triggering effects related to weak seismicity due to a high stress accumulation rate (1 KPa per hour) in the SSHPS area. A connection between earth tides and catastrophic events, such as gas emissions in high amounts on mining sites, is discussed. Having analysed the surface monitoring records taken in South Primorye in September 2017, we conclude that underground nuclear explosions in North Korea in this period did not cause any significant displacement of the surface in this most southerly region of the Russian Far East territories.